2018
DOI: 10.1177/0886260518787807
|View full text |Cite
|
Sign up to set email alerts
|

Forcible Rape and Adolescent Friendship Networks

Abstract: Studies have found that sexual victimization can adversely affect an adolescent's psychological well-being, physical health, and behavior. Little is known, however, about how friendships are influenced by such victimization. Drawing on research on sexual violence and the salience of peers among adolescents, the current study extends prior work by examining the effects of forcible rape on adolescent social networks. Using a subsample of females from the National Longitudinal Study of Adolescent to Adult Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 96 publications
(132 reference statements)
2
4
0
Order By: Relevance
“…Alternatively, peers could become overwhelmed or feel inadequately prepared to deal with the victimization of their peers, and in turn withdraw support. Similar findings have surfaced with perceived support, number of friends, and connectedness after victimization (Smokowski et al, 2014;Tomlinson et al, 2021;Wallace & Ménard, 2017), such that support decreased over time. For example, forcible rape was associated with lower levels of popularity and centrality in friendship networks among adolescent girls, but importantly, attachment to friends and school, mediated these relationships (Tomlinson et al, 2021).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Alternatively, peers could become overwhelmed or feel inadequately prepared to deal with the victimization of their peers, and in turn withdraw support. Similar findings have surfaced with perceived support, number of friends, and connectedness after victimization (Smokowski et al, 2014;Tomlinson et al, 2021;Wallace & Ménard, 2017), such that support decreased over time. For example, forcible rape was associated with lower levels of popularity and centrality in friendship networks among adolescent girls, but importantly, attachment to friends and school, mediated these relationships (Tomlinson et al, 2021).…”
Section: Discussionsupporting
confidence: 68%
“…Similar findings have surfaced with perceived support, number of friends, and connectedness after victimization (Smokowski et al, 2014;Tomlinson et al, 2021;Wallace & Ménard, 2017), such that support decreased over time. For example, forcible rape was associated with lower levels of popularity and centrality in friendship networks among adolescent girls, but importantly, attachment to friends and school, mediated these relationships (Tomlinson et al, 2021). It is also important to mention that secondary trauma could play a role.…”
Section: Discussionsupporting
confidence: 68%
“…Understanding the connections survivors still have to their perpetrators post-assault and how that impacts their social networks is also important in understanding recovery, social support, and/or behavioral changes post-assault. In a study of adolescent female rape victims, Tomlinson, Mears, Turanovic, and Stewart (2018) found that forcible-rape victims' popularity and centrality significantly decreased within their adolescent friendship networks. These effects were partially mediated by levels of depression and social attachments and illustrate how sexual assault can impact not only the survivor, but the survivor's social networks and possible supports (Tomlinson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of adolescent female rape victims, Tomlinson, Mears, Turanovic, and Stewart (2018) found that forcible-rape victims' popularity and centrality significantly decreased within their adolescent friendship networks. These effects were partially mediated by levels of depression and social attachments and illustrate how sexual assault can impact not only the survivor, but the survivor's social networks and possible supports (Tomlinson et al, 2018). Another study comparing acknowledged (n=125) and unacknowledged rapes (n=194) in college victims of alcohol-facilitated assaults found that almost 30% of their total sample (n=93) continued their relationship with the perpetrator post-assault (Littleton, Grills, Layh, & Rudolph, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Operating within the gender binary, one in three females and one in six males are sexually assaulted during their lifetime, with most victimizations occurring during childhood or adolescence (Finkelhor et al, 2014;Tomlinson et al, 2018). Adolescents, specifically between the ages of 16 and 19, are four times more likely to be sexually assaulted as compared to any other age-group and continue to experience the highest rates of sexual victimization of all age groups (Campbell et al, 2013;Crawford-Jakubiak et al, 2017;Giroux et al, 2018;Martsolf et al, 2010;Trotman et al, 2016).…”
mentioning
confidence: 99%